Co‐morbidities in Chinese children with attention deficit/hyperactivity disorder and reading disabilities. (22nd December 2017) - Wang, Li‐Chih; Chung, Kevin Kien Hoa
Abstract : The co‐morbidity of attention deficit/hyperactivity disorder (ADHD) and reading disorder (RD) is more frequent than expected. This investigation assessed the potential uniqueness of the co‐morbidity of ADHD and RD and extended existing findings to the Chinese language. A parallel group design with a post hoc analysis of group differences was employed to compare 4 groups of children (30 with ADHD, 33 with RD, 28 with ADHD + RD, and 30 typically developing) regarding their reading comprehension, attention, reading‐related abilities, and cognitive abilities. The findings indicated that children with RD and/or ADHD symptom(s) exhibited diverse cognitive profiles, and the distinguishing factor contributed to different inhibitions. Additionally, Chinese‐speaking children with the co‐morbid symptoms of RD and ADHD demonstrated greater deficits in auditory working memory and rapid naming than did the pure‐deficit groups. Furthermore, although problems with phonological awareness were similar between the 2 groups, the deficiency of orthographic knowledge was more severe in children with RD than in the co‐morbid group. The ADHD + RD group's cognitive and reading‐related abilities displayed a relatively complicated pattern that should be considered in the diagnosis of either RD or ADHD and their remediation design.